Sexing the soldier : the politics of gender and the contemporary British Army - Woodward, Rachel (Transformations., 2007)
Sexing the Soldier takes a critical look at how gender is understood within the contemporary British Army. Drawing on original research, this book argues that dominant ideas about gender, evident in areas as diverse as policy documents and cultural pract.